THE INFLUENCE OF LEADERSHIP STYLE ON THE PERFORMANCE OF EMPLOYEES AT CLASS IIB MAROS CORRECTIONAL INSTITUTION - Jusrawati; Nurman, Anwar, Agung Widhi Kurniawan, Burhanuddin (Adisam Publisher, 2025)
This research aims to determine the influence of leadership style on employee performance at the Class IIB Maros Correctional Institution. This research uses a quantitative method of an associative nature, with a population of 57 people who are also the sample for the study. The data collection techniques used were questionnaires and documentation. The data analysis technique used is descriptive statistics and for inferential statistical analysis using simple linear regression with SPSS version 25. The results of this study indicate that the leadership style falls into the effective category based on indicators of decision-making ability, motivational ability, communication ability, ability to control subordinates, and ability to control emotions. The performance of employees at the Class IIB Maros Correctional Institution falls into the high category based on indicators of service orientation, integrity, commitment, discipline, cooperation, and leadership. Based on the results of simple regression analysis, there is no significant influence of Leadership Style on the Performance of Employees at the Class IIB Maros Correctional Institution.